Fenomena Tradisi Puasa Nisfu Sya’ban Lingkungan Delapan Kelurahan Binjai Serbangan Kecamatan Air Joman Kabupaten Asahan (Studi Living Hadis - Nasution, Sulthoni Karim (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
The tradition of Ni¡fu Sha'ban fasting has long been rooted in Indonesian society, although there are questions among the ulama regarding the validity of the hadiths that form the basis of this practice. This phenomenon reflects the dynamics of Islam in Indonesia which combines "normative Islam" and "mystical Islam" in people's religious expressions, as expressed by Woodward. Azra added that the development of Islam in Indonesia cannot be separated from the process of acculturation with local culture, so that the practice of Ni¡fu Sya'ban fasting can be seen as one of the results of this process. In various areas, such as Neighborhood Eight, Binjai Serbangan Subdistrict, Asahan Regency, Ni¡fu Sha'ban fasting has become a well-maintained tradition, even though it contains the quality of the underlying hadiths. In this context, this research aims to analyze the hadiths regarding fasting Ni¡fu Sha'ban and the extent to which the quality of these hadiths is recognized in local society. The research uses the Living Hadith approach to explore the understanding and implementation of hadith in community traditions. Through in-depth interviews and participant observation, this research found that Ni¡fu Sha'ban fasting is practiced with the belief in certain virtues, such as forgiveness of sins and increase in rewards. However, the quality of the hadith related to the Ni¡fu Sha'ban fast is the subject of debate, especially with regard to its validity and status among the ulama. Overall, the research results show that the hadiths about fasting Ni¡fu Sha'ban are Daif, although the hadiths about fasting Ni¡fu Sha'ban in the Eighth Circle are considered valid by some people, there are differences of opinion regarding their validity and acceptance by ulama. This reflects the dynamics between hadith texts and local practices that develop in society. This research contributes to the study of Living Hadith by enriching understanding of how hadith is implemented in local traditions in Indonesia, especially in relation to the quality of hadith which is the basis of community religious practice.